Differences in pelvic floor morphology between continent, stress urinary incontinent, and mixed urinary incontinent elderly women: An MRI study. Issue 4 (1st March 2015) - Pontbriand‐Drolet, Stéphanie; Tang, An; Madill, Stephanie J.; Tannenbaum, Cara; Lemieux, Marie‐Claude; Corcos, Jacques; Dumoulin, Chantale
Abstract : Aims: To compare magnetic resonance imaging (MRI) of the pelvic floor musculature (PFM), bladder neck and urethral sphincter morphology under three conditions (rest, PFM maximal voluntary contraction (MVC), and straining) in older women with symptoms of stress (SUI) or mixed urinary incontinence (MUI) or without incontinence. Methods: This 2008–2012 exploratory observational cohort study was conducted with community‐dwelling women aged 60 and over. Sixty six women (22 per group), mean age of 67.7 ± 5.2 years, participated in the study. A 3 T MRI examination was conducted under three conditions: rest, PFM MVC, and straining. ANOVA or Kruskal–Wallis tests (data not normally distributed) were conducted, with Bonferroni correction, to compare anatomical measurements between groups. Results: Women with MUI symptoms had a lower PFM resting position (M‐Line P = 0.010 and PC/H‐line angle P = 0.026) and lower pelvic organ support (urethrovesical junction height P = 0.013) than both continent and SUI women. Women with SUI symptoms were more likely to exhibit bladder neck funneling and a larger posterior urethrovesical angle at rest than both continent and MUI women ( P = 0.026 and P = 0.008, respectively). There were no significant differences between groups on PFM MVC or straining. Conclusions: Women with SUI and MUI symptoms present different morphological defects at rest. These observations emphasize the need to tailor UI interventions to specific pelvic floor defects and UI type in older women. Patient summary: Older women with UI demonstrate different problems with their pelvic organ support structures depending on the type of UI. These new findings should be taken into consideration for future research into developing new treatment strategies for UI in older women. Neurourol. Urodynam. 35:515–521, 2016 . © 2015 Wiley Periodicals, Inc.